Prognostic factors for survival and ambulatory status at 8 weeks with metastatic spinal cord compression in the SCORAD randomised trial. (August 2022) - Hoskin, Peter J.; Hopkins, Kirsten; Misra, Vivek; Holt, Tanya; McMenemin, Rhona; McKinna, Fiona; Madhavan, Krishnaswamy; Bates, Andrew; O'Rourke, Noelle; Lester, Jason F.; Sevitt, Tim; Roos, Daniel; et al.
Highlights: A prognostic model for recovery of mobility and survival in metastatic spinal cord compression. Recovery of mobility is greatest in those ambulant with primary breast or prostate cancer. Survival is greatest in ambulant females with breast cancer, and no extraskeletal metastases. Abstract: Background: Metastatic spinal cord compression (MSCC) carries a poor prognosis and management is based on the likelihood of maintaining mobility and predicted survival. Patients and method: SCORAD is a randomised trial of 686 patients comparing a single dose of 8 Gy radiotherapy with 20 Gy in 5 fractions. Data was split into a training set (412, 60%) and a validation set (274, 40%). A multivariable Cox regression for overall survival (OS) and a logistic regression for ambulatory status at 8 weeks were performed in the training set using baseline factors and a backward selection regression to identify a parsimonious model with p ≤ 0.10. Receiver Operating Characteristic (ROC) analysis evaluated model prognostic performance in the validation set. Validation of the final survival model was performed in a separate registry dataset ( n = 348). Results: The survival Cox model identified male gender, lung, gastrointestinal, and other types of cancer, compression at C1–T12, presence of non-skeletal metastases and poor ambulatory status all significantly associated with worse OS (all p < 0.05). The ROC AUC for the selected model was 75% (95%CI: 69–81) in the SCORAD validation set and 68% (95%CI: 62–74) in the external validation registry data. The logistic model for ambulatory outcome identified primary tumour breast or prostate, ambulatory status grade 1 or 2, bladder function normal and prior chemotherapy all significantly associated with increased odds of ambulation at 8 weeks (all p < 0.05). The ROC AUC for the selected model was 72.3% (95% CI 62.6–82.0) in the validation set. Conclusions: Primary breast or prostate cancer, and good ambulatory status at presentation, are favourable prognostic factors for both survival and ambulation after treatment.